IDENTIFICATION OF FAMILY ENGAGEMENT IMPLEMENTATION PROGRAM IN EARLY CHILDHOOD EDUCATION UNIT - Latifah, Julia Rahma; Rachmawati, Yeni; Rudiyanto, Rudiyanto (Edukids: Jurnal Pertumbuhan, Perkembangan, dan Pendidikan Anak Usia Dini, 2021)
This research is motivated by the lack of family engagement participation in programs held by the institute of early childhood education. This research is aimed at discovering various family engagement programs in the Early Childhood Education (ECE) unit, supporting factors and barriers to the implementation of the family engagement program, and the benefits of the family engagement program in the ECE unit. The method employed in this research is literature review. Data were collected by studying various journals, books, and other relevant documents from various national and international web. The data analysis technique employed in this research is the MilesHuberman’s model by utilizing stages of analysis process consisting of data reduction, data organization, data display, and data interpretation. The research found that there are some family engagement programs, such as parents meeting to examine the science of parenting, communication development, volunteering in school programs, being involved in decision making, supporting learning at home activities, and collaborating with community. Factors supporting the implementation of the family engagement program in ECE are parents' commitment, solid parent-teacher relationships, parents' awareness, and parents' educational background. On the other hand, factors that become barriers in implementing the program are limited time, limited parents’ financial capability, parents’ low levels of education background, parents’ insecurity, and parents’ lack of understanding of the importance of the program. The benefit of family engagement program perceived by parents is gaining knowledge, information, and confidence in parenting. Furthermore, the program increases children’s performance, learning motivation, discipline, and creates alignment between learning at home and in school